2017
DOI: 10.1002/cjce.22968
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of sugarcane bagasse in a fixed bed reactor: Influence of operational conditions in the distribution of products

Abstract: This work experimentally evaluated the pyrolysis of sugarcane bagasse in a fixed bed reactor in order to obtain products useful in energy applications. The raw material was characterized to understand its behaviour during the thermal degradation process. The effects of operating conditions on mass yields of bio‐oil, biochar, and non‐condensable gases were investigated. The operating variables studied were temperature (400 to 700 °C), particle size (<0.5 mm, 0.5–1.0 mm, and 1.0–1.41 mm), heating rate (5, 10, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Pyrolysis is a decomposition process that occurs with heat in an oxygen-free environment. In the pyrolysis process, the lignocellulosic biomass that contains cellulose, hemicellulose, and lignin is transformed into carbon-rich solid (char) and liquid (bio-oil) products (Gonçalves et al, 2017; Hopa et al, 2016; Naqvi and Naqvi, 2018; Yusup et al, 2015). Co-pyrolysis and pyrolysis are the same process; the only difference is that two or more different substances are used as raw material in co-pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis is a decomposition process that occurs with heat in an oxygen-free environment. In the pyrolysis process, the lignocellulosic biomass that contains cellulose, hemicellulose, and lignin is transformed into carbon-rich solid (char) and liquid (bio-oil) products (Gonçalves et al, 2017; Hopa et al, 2016; Naqvi and Naqvi, 2018; Yusup et al, 2015). Co-pyrolysis and pyrolysis are the same process; the only difference is that two or more different substances are used as raw material in co-pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…(Ehman et al, 2020;Miranda, Bica, Nachtigall, Rehman, & Rosa, 2013). After this peak, there is an exothermic rise close to 400 C attributed to the degradation of lignin (Gonçalves et al, 2017;Miyahara et al, 2018). In this way, it is suggested that these differences in the FTIR spectra and thermal behavior represent effects of solubilization and concentration of biomass components, with no chemical changes during the hydrothermal process.…”
Section: Effect Of Hydrothermal Treatment In the Physical-chemical Characteristics Of Scbmentioning
confidence: 95%
“…The high levels of carbon in biochar are correlated with the elevated trends in fixed carbon. Furthermore, due to the presence of mineral components remaining after carbonization, biochar exhibits higher ash levels (up to 23 wt%) compared to bagasse (1-6%) [79,[81][82][83][84][85]. Lastly, in contrast to bagasse, which typically contains volatile matter levels of up to 85 wt%, biochar displays a reduced volatile matter content of up to 57 wt%.…”
Section: Composition Of Sugarcane Bagasse Biocharmentioning
confidence: 99%